THE IMPORTANCE OF RISK FACTORS IN THE DEVELOPMENT OF ARTERIOSCLEROSIS IN UNCONTROLLED ARTERIAL HYPERTENSION (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
The article discusses the effect of uncontrolled arterial hypertension on the development of arteriosclerosis and analyzes the main risk factors. It is noted that a prolonged increase in blood pressure leads to morphological changes in the vascular wall, endothelial dysfunction, lipid metabolism disorders and an increase in blood viscosity. In addition, factors such as age, heredity, unbalanced diet, lack of physical activity and stress accelerate the development of arteriosclerosis. The paper emphasizes the importance of blood pressure control and risk factor correction for the prevention of cardiovascular disease.